EVIDENCE BASED CASE REPORT (EBCR): PENGARUH INISIASI MENYUSU DINI PADA BAYI BARU LAHIR TERHADAP PENCEGAHAN HIPOTERMI (Politeknik Kesehatan Kemenkes Bandung, 2023)
Background: Early initiation of breastfeeding is the ability of a baby to start breastfeeding on its own soon after birth. Hypothermy is one of the effects of IMD not done on newborns which can cause low infant temperature resulting in slowed metabolic and physiological processes. IMD was found to be a safe and effective method to prevent hypothermia in newborns which can be one of the nonpharmacological approaches as it is a cost effective intervention and easy to implement in any setting as it does not require additional facilities. Purpose: The application of evidence-based practice aims to determine the effect of IMD in preventing hypothermia in newborns. Method: This EBCR writing method is by searching for evidence through data based on Pubmed and Google Scholar with a publication year of 2017-2022 obtained 1 article for critical review. Results: The results of the application of IMD in this case showed that there was an increase in temperature after IMD was carried out, namely 36.2oC (pre) to 36.7oC after IMD. Conclusion: IMD is an effective method for the prevention of hypothermia in newborns.